2017
DOI: 10.1371/journal.pone.0174966
|View full text |Cite
|
Sign up to set email alerts
|

Safety aspects of atmospheric pressure helium plasma jet operation on skin: In vivo study on mouse skin

Abstract: Biomedical applications of plasma require its efficacy for specific purposes and equally importantly its safety. Herein the safety aspects of cold plasma created with simple atmospheric pressure plasma jet produced with helium gas and electrode discharge are evaluated in skin damage on mouse, at different duration of exposure and gas flow rates. The extent of skin damage and treatments are systematically evaluated using stereomicroscope, labelling with fluorescent dyes, histology, infrared imaging and optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 42 publications
(42 reference statements)
0
43
0
Order By: Relevance
“…Also, mouse skin temperature was evaluated in-vivo experiment and temperature increase was reported about 1 ± 0.3 ° c , showing that this change in temperature cannot inflict any thermal damages. In this regard, the result of H&E staining after plasma exposure proves that cold plasma doesn’t cause any thermal damages 73 .…”
Section: Discussionmentioning
confidence: 91%
“…Also, mouse skin temperature was evaluated in-vivo experiment and temperature increase was reported about 1 ± 0.3 ° c , showing that this change in temperature cannot inflict any thermal damages. In this regard, the result of H&E staining after plasma exposure proves that cold plasma doesn’t cause any thermal damages 73 .…”
Section: Discussionmentioning
confidence: 91%
“…In addition to in vitro research, plasma-associated side effects and risk potential were also evaluated in animal experiments. Kos et al [40] investigated direct and indirect damage mechanisms in a mouse model and concluded that plasma application (jet system) is not as safe as described by numerous other authors. However, critical analysis of this study shows various limitations.…”
Section: Discussionmentioning
confidence: 97%
“…Ozone has a role in the formation of biologically active ROS and RNS in aqueous media, which may be responsible for cell death [ 61 , 62 ]. Atomic oxygen (O) (including the ground state and all the excited states) is believed to have a significant effect on cells [ 63 , 64 ]. Superoxide (O 2 − ) generated by plasma can activate mitochondrial-mediated apoptosis by changing mitochondrial membrane potential and simultaneously up-regulates pro-apoptotic genes and down-regulates anti-apoptotic genes for activation of caspases resulting in cell death [ 65 ].…”
Section: Discussionmentioning
confidence: 99%